Heteroleptic magnesium complexes containing amidinate and aminoalkoxy ligands. (24th November 2015) - Kim, Hyo-Suk; George, Sheby Mary; Jung, Eun Ae; Park, Bo Keun; Son, Seung Uk; Kim, Chang Gyoun; Chung, Taek-Mo
Graphical abstract: Design and synthesis of new heteroleptic magnesium complexes, containing aminoalkoxy and amidinate ligands were demonstrated. The complexes formed as dimers, where aminoalkoxy ligands play the role of bridging two magnesium metal centers. Abstract: New heteroleptic magnesium complexes, [Mg(dmamp)(η 2 -MeC(NEt)(N t Bu))]2 (1 ), [Mg(dmamp)(η 2 -MeC(N i Pr)2 ]2 (2 ), and [Mg(dmamp)(η 2 -MeC(N t Bu)2 ]2 (3 ), containing a combination of amidinate and aminoalkoxy ligands were synthesized and characterized by NMR, FT-IR, elemental analysis, and thermogravimetric analysis (TGA). The single-crystal X-ray diffraction study of these complexes (1 –3 ) reveals that all complexes were formed as dimers where the aminoalkoxy ligand acts as the bridge between the two metal centers.